Pengaruh Profitabilitas, Leverage, Komite Audit, dan Ukuran Perusahaan terhadap Audit Report Lag: Studi Empiris pada Perusahaan Property & Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2021–2023 - Nawang Sholekhah; Indah Permata Dewi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the effect of profitability, leverage, audit committee, and firm size on audit report lag in property and real estate companies listed on the Indonesia Stock Exchange. A quantitative approach with purposive sampling was applied, resulting in a sample of 71 companies over the 2021–2023 period, totaling 120 observations. Data analysis was conducted using multiple linear regression with SPSS software. The results indicate that profitability and leverage have a significant negative effect on audit report lag, suggesting that companies with higher profitability and lower leverage tend to complete their audit processes more promptly. In contrast, the audit committee and firm size do not show a significant effect on audit report lag. These findings suggest that financial performance factors play a more dominant role in determining the timeliness of audit reporting than corporate governance mechanisms and firm size. This study contributes to the literature on financial reporting and corporate governance and offers practical implications for managers and auditors in improving the efficiency of audit report completion.